2016
DOI: 10.1089/sur.2015.192
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Panton-Valentine Leukocidin-Positive Methicillin-ResistantStaphylococcus aureusNasal Carriage among Egyptian Health Care Workers

Abstract: This is the first report on nasal carriage of pvl-positive MRSA among Egyptian health care personnel. High carriage rate of MRSA among health care personnel has been attributed mainly to poor hand hygiene compliance and non-judicious use of antibiotics. Improving compliance, reducing antibiotic overuse, screening for carriers, and decolonization are recommended strategies for reducing the spread of MRSA. Multiplex PCR could be used for confirmation of results obtained by conventional phenotypic methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 36 publications
3
17
1
3
Order By: Relevance
“…Nasal colonization with S. aureus plays an essential role in transmission of infections [2,4]. Of particular importance are the nasal carriers of MRSA among medical staff who possess a higher risk for transmission of nosocomial infections [39][40][41]. MRSA is regarded as the most serious infection in hospitals [42].…”
Section: Discussionmentioning
confidence: 99%
“…Nasal colonization with S. aureus plays an essential role in transmission of infections [2,4]. Of particular importance are the nasal carriers of MRSA among medical staff who possess a higher risk for transmission of nosocomial infections [39][40][41]. MRSA is regarded as the most serious infection in hospitals [42].…”
Section: Discussionmentioning
confidence: 99%
“…In any case, the mecC -MRSA human prevalence detected in most of the studies was very low. Several studies did not identify any mecC -positive S. aureus among included human isolates/samples ( Table 2 ) [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. In studies in which this gene was detected ( Table 1 ), the prevalence identified, considering the total number of isolates/samples included, was < 1% in most of the cases [ 24 , 27 , 28 , 29 , 32 , 33 , 37 , 40 , 41 , 42 , 43 ], similar to that identified in the first study in which mecC was discovered (approximately 0.04%) [ 16 ].…”
Section: Detection Of Mecc -Mrsa Isolates In Humentioning
confidence: 99%
“…Panton Valentine leukocidin (PVL), is encoded by lukF-PV and lukS-PV genes, produced by some S. aureus strains, is one of the significant cytotoxins and responsible for dermal and soft tissue infections (Genestier et al, 2005). Limited data available about the epidemiology of Egyptian PVL -positive MRSA strains (Helal et al, 2012 andHefzy et al, 2016) The present study aimed to assess the relatedness of MRSA isolates and the potential routes of transmission using PCR-RFLP by examining environmental samples and HCWs nasal swabs in relation to MRSA recovered from patients of Hemodialysis Unit of El Zagazig General Hospital, Sharqia, Egypt. In addition, the presence of PVL staphylococcal virulence factor gene was investigated.…”
Section: Introductionmentioning
confidence: 99%